Infrequent and Potentially Missed Cause of Hypoxemia in an Infant - Elgabaly, Elham A (Cureus, 2019)
Neuroendocrine cell hyperplasia of infancy (NEHI) is a recently reported condition and commonly missed. A general pediatrician who encounters an infant with an insidious onset of breathlessness, hypoxemia, and failure to thrive should think through a diagnosis of NEHI when common respiratory diseases are excluded. Lung biopsy is regarded as the diagnostic gold standard for NEHI and typically demonstrates increased numbers of neuroendocrine cells (NECs) in otherwise near-normal lung tissues. However, classic high-resolution computed tomography (HRCT) findings can enable to establish the diagnosis without the need for a biopsy. This case shows typical chest imaging findings of NEHI with a brief review of the literature.